PERSEPSI MAHASISWA TENTANG PEMBELAJARAN MATA KULIAH BANK DAN LEMBAGA KEUANGAN LAINNYA DENGAN PENDEKATAN KONTEKSTUAL - Sri Hermuningsih; Kristi Wardani (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
The learning method subjects Banks and Other Financial Institutions in Higher Education in general is still ongoing in the classical form of face-to-face in the classroom between students and professors who refers to the reference/guide Bank and Other Financial Institutions. The learning process causes less students gain learning experience in making investment in the Bank and Other Financial Institutions. Efforts to improve the learning process with the development model of contextual approach in learning subjects Banks and Other Financial Institutions. The purpose of this study was to assess the students' perceptions about learning subjects Banks and Other Financial Institutions with a contextual approach. The population in this study were students Management and Accounting Faculty of Economics, which cover subjects UST Banks and Other Financial Institutions. The research sample number of 50 students.The method of analysis with behavioral approach system usage information Technology Acceptance Model (TAM). The results show that the descriptive aspects: (1) perceived ease of use were high, average scores obtained for 80.2% (2) perceived ease of use is high, the average score of 91.3%; (3) attitude toward using higher category, the average score of 90% ,; while the aspect (4) Behavioral Intention to Use categorized as high, averaging a score of 91.3%; and (5) the actual technology usage were high, averaging a score of 95.2%. Perception of students in the learning of subjects Banks and other financial institutions with a contextual approach to feel the benefits, ease of use and attitude is positive and fun and not boring. Keywords: Perception, contextual approach, the Technology Acceptance Model (TAM).